1992
DOI: 10.1001/archderm.1992.01680150069008
|View full text |Cite
|
Sign up to set email alerts
|

Middermal Wound Healing

Abstract: We conclude that the focused pulsed CO2 laser is capable of precisely and bloodlessly ablating skin with conservation of residual subjacent adnexal elements, minimal early interference with epibolic epithelial outgrowth, and no pathologic effects on the wound healing process. Pulsed CO2 lasers may be a valuable instrument for the conservative ablation of skin and skin lesions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

1993
1993
2015
2015

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(7 citation statements)
references
References 47 publications
1
6
0
Order By: Relevance
“…Epidermal cell outgrowth from C02 laser cut skin explants was delayed approximately 3 days compared with scalpel cut explants, with a similar rate of growth once initiated [79]. A similar 3-day delay in epithelialization was seen in GO, laser-ablated wounds compared with dermatome-created wounds [80].…”
Section: Healing After Laser Weldingmentioning
confidence: 76%
“…Epidermal cell outgrowth from C02 laser cut skin explants was delayed approximately 3 days compared with scalpel cut explants, with a similar rate of growth once initiated [79]. A similar 3-day delay in epithelialization was seen in GO, laser-ablated wounds compared with dermatome-created wounds [80].…”
Section: Healing After Laser Weldingmentioning
confidence: 76%
“…The delay in healing wounds of equal depth produced by burns was interpreted as a direct result of thermal tissue destruction extending considerably beyond the boundaries of the nominal defects (Schaffer et al 1997). In another study, a delay in reepithelialization was observed in wounds produced by laser ablation relative to wounds produced by dermatome (Green et al 1992). Further differences between laser resurfacing and ablative methods in extent of wound contraction were demonstrated in wounds of the same total depth of injury (Ross et al 2000).…”
Section: Energy Source Used To Generate Injurymentioning
confidence: 98%
“…Many studies treating facial wrinkles have been reported, and excellent results have been obtained after laser treatment [4±7]. Studies evaluating the healing process after laser treatment of human skin [8±12] or animal skin have been reported [13,14]. However, no studies that used animal models for the healing process of wrinkle smoothing have been published, even though such studies may be important for understanding the mechanism of wrinkle smoothing and improvement elicited by laser-therapy.…”
Section: Introductionmentioning
confidence: 99%